Complete blood cell count components and coronary slow-flow phenomenon - Arjmand N; Dehghani MR (Dove Medical Press, 2016)
Nasim Arjmand, Mohammad Reza Dehghani Department of Cardiology, Seyyed-al-Shohada Heart Center, Urmia University of Medical Sciences, Urmia, IranDespite the implementation of preventive strategies, ischemic heart disease and stroke remain the main causes of mortality and morbidity worldwide.1,2 Of the cardiovascular diseases, coronary slow-flow phenomenon (CSFP), with a prevalence rate of 1%–7% among patients undergoing diagnostic coronary angiography, has been found to be associated with cardiovascular events, including cardiac arrhythmia and acute coronary syndrome.3–5 However, the potential mechanisms involved in the pathogenesis of CSFP remain unknown. Microvascular and endothelial dysfunctions, inflammation, diffuse atherosclerosis, and increased platelet aggregability have been reported to be the main possible etiologies for CSFP.6,7View original paper by Atlas and colleagues.